2022
DOI: 10.3389/fvets.2022.854905
|View full text |Cite
|
Sign up to set email alerts
|

High Genetic Diversity of Porcine Sapovirus From Diarrheic Piglets in Yunnan Province, China

Abstract: As one of the most important enteric viruses, sapovirus (SaV) can infect humans and a variety of animals. Until now, 19 SaV genogroups have been identified, among which 4 from human (GI, GII, GIV, and GV) and 8 from swine (GIII, GV–GXI). Porcine sapovirus (PoSaV) GIII has been prevalent in China; however, the status of PoSaV infection in Yunnan province remains unknown. In this study, 202 fecal samples were collected from piglets associated with outbreaks of acute diarrhea in Yunnan between January and May 202… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

3
2
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 7 publications
(5 citation statements)
references
References 49 publications
3
2
0
Order By: Relevance
“…In this study, the positive rate was 9.8%, which was similar to that of positive rates reported in China (9%) [32], the Czech Republic (10.2%) [13], and Slovakia (clinical healthy pigs: 8.4%; diarrhoeic pigs: 10%) [33]. The currently positive rate was lower than that of positive rates reported in the USA (62%) [34], Yunnan city of China (35.2%) [21], and Brazil (23.7%) [35]. The differences in percentage rates might have been due to the different locations and times of sampling.…”
Section: Discussionsupporting
confidence: 81%
See 1 more Smart Citation
“…In this study, the positive rate was 9.8%, which was similar to that of positive rates reported in China (9%) [32], the Czech Republic (10.2%) [13], and Slovakia (clinical healthy pigs: 8.4%; diarrhoeic pigs: 10%) [33]. The currently positive rate was lower than that of positive rates reported in the USA (62%) [34], Yunnan city of China (35.2%) [21], and Brazil (23.7%) [35]. The differences in percentage rates might have been due to the different locations and times of sampling.…”
Section: Discussionsupporting
confidence: 81%
“…Furthermore, some caliciviruses can spread to animals [ 3 , 14 , 19 ]. Although evidence of transmission of swine in human Sapoviruses remain unclear, the likelihood that they act as a reservoir species is increased by the prevalence of infection and recombination in pigs [ 6 , 20 , 21 , 22 ]. However, there have never been any proven instances of PoSaVs spreading from pigs to humans.…”
Section: Introductionmentioning
confidence: 99%
“…Herein, we present the novel PoSaV isolate SHCM/Mega2023, characterized by recombination with MK962338 (major parent) and KT922089 (minor parent), with a breakpoint identified at 2969–5132 nt in the RdRp-capsid junction region. The results suggested that intra-genogroup recombination may occur between field GIII strains, a premise which was consistent with most of the recombination events [ 15 , 33 , 34 , 35 , 36 ]. Available sequences showed that Yunnan PoSaV-GIII strain YNAN might be the only recombinant with breakpoints located in the VP1 region, which is important for immunogenicity [ 34 ].…”
Section: Discussionsupporting
confidence: 67%
“…The results suggested that intra-genogroup recombination may occur between field GIII strains, a premise which was consistent with most of the recombination events [ 15 , 33 , 34 , 35 , 36 ]. Available sequences showed that Yunnan PoSaV-GIII strain YNAN might be the only recombinant with breakpoints located in the VP1 region, which is important for immunogenicity [ 34 ]. And it also had evolved via an intra-genogroup recombination event.…”
Section: Discussionsupporting
confidence: 67%
“…These data would provide database for the prevention and control of clinical porcine diarrhea disease. (Wang et al, 2019;Liu X et al, 2022;Qiu et al, 2022)…”
mentioning
confidence: 99%